235k views
2 votes
Find the equation of the graph

Find the average rate of change from x = 5 to x = 7

Find the equation of the graph Find the average rate of change from x = 5 to x = 7-example-1
User Leftjoin
by
5.6k points

1 Answer

5 votes

Answer: y=-(x-6)(x-8)

Average rate of change: 2

Explanation:

Graph facing downward, so equation is negative

Since the equation is quadratic, the degree is 2.

When you look at the graph, you see the values of x when y=0

x=6 ==> y=0

x=8 ==> y=0

Equation: y=-(x-6)(x-8) ==> add the negative sign to show the equation is going down.

x=5 ==> y=-3 ==> (5, -3)

x=7 ==> y=1 ==> (7, 1)

Slope formula: m=(y2-y1)/(x2-x1)

m=(1-(-3))/(7-5)

m=(1+3)/(2)

m=4/2

m=2 ==> average rate of change

User Enguerranws
by
5.8k points